Efecto del riego por aspersión para la optimización del rendimiento en el cultivo del cacao (Theobroma cacao) variedad CCN-51 en época seca, en el Cantón Quinsaloma, provincia de Los Ríos. - Gaibor Pozo, Lisbeth Roxanna (2017)
The present research was carried out the cultivation of cocoa (Theobroma cacao) CCN-51 in the dry season Quinsaloma canton - province of Los Ríos, the area presents a humid tropical climate with an annual average temperature is 24.8 ° C, average precipitation Annual of 2252.5 mm, 84% of relative humidity, annual average heliofanía of 894 hours. The objectives were; To determine the evapotranspiration of the crop as a means for the definition of the frequency of irrigation. Define the amount of irrigation water that meets the water requirements of the crop culminated by evapotranspiration and agroclimatic conditions. Carry out the economic analysis according to the frequency of irrigation and yield of the cocoa crop. The treatments were: Replenishment of the water to the consumption of 40, 60, 80%, using as a control treatment the irrigation (spraying) by the farmer (two hours, once a week) and a treatment without irrigation application. We used the completely randomized design with three replicates and for the comparison of means the Duncan test to 95%. The percentage of flowering fertility, number of ears, ear weight, shell weight, mucilage weight, number of almonds per ear, wet and dry weight of almonds, yield and economic analysis were evaluated. The analysis and interpretation of the results concludes: The highest percentage of fertile flowers 53.72% was obtained when irrigation was applied to 40% of the water available in the soil. In the variable of the weight of harvested healthy ears obtained the highest average with 630g with the application of the treatment to 40% of the ETC of water replenishment. With the replacement of water at 40% of consumption, almonds reached the highest weight averages with 190g and 70g per ear, thus increasing production. The highest number of cobs was reached with the replacement of the water consumption to 40% of the sheet, presented 70 cobs more than the control without replacement The frequency of irrigation to 40% of the water sheet consumed produced the highest yield and the highest Net benefit with $ 659.00 in the first harvest season, $ 109 than the no irrigation witness. Key words: irrigation, cocoa, redeeming, economic analysis.